The Influence of Science Process Skills, Digital Literacy and Students' Critical Thinking Skills on Physics Learning: A Mixed Method Study - Darmaji Darmaji; Astalini Astalini; Yusnidar Yusnidar; Dwi Agus Kurniawan; Sri Wina Oktavia (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to examine the effects of integrating digital literacy into optical instruments learning on students’ science process skills and critical thinking ability. Methodology: A mixed methods approach with an explanatory sequential design was employed. The quantitative phase involved 60 students in Senior High School Jambi, selected through purposive sampling. Data were collected using a digital literacy questionnaire, a science process skills observation sheet, and a critical thinking test, and analyzed using multiple linear regression. The qualitative phase was conducted through semi-structured interviews to support and explain the quantitative findings. Main Findings: The results indicate that digital literacy has a significant positive effect on science process skills and critical thinking ability in optical instruments learning. Qualitative findings reveal that digital simulations and digital-based inquiry activities enhance students’ engagement, analytical reasoning, and understanding of optical concepts. Novelty/Originality of this study: This study highlights the role of digital literacy as an integrative framework that supports scientific inquiry and higher-order thinking in physics education.